Implementation of Vocabulary Teaching Using the Educaplay Word Search Puzzle - Siti Fahimatul Ilmia; Agus Khunaifi; Tuti Qurrotul Aini; Muhammad Atif Awadh Ramadhan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to describe the application of Arabic vocabulary learning using the digital media Educaplay Word Search Puzzle at Madrasah Tsanawiyah Negeri 2 Semarang City and analyze the activities and responses of students during the learning process. This study uses a descriptive qualitative approach with the research subjects of an Arabic teacher and grade VII students who are directly involved in learning activities. Data collection techniques include observation of the learning process, interviews with teachers and students, and documentation as supporting data. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the use of Educaplay Word Search Puzzle media can create an interactive, collaborative, and participatory learning atmosphere. Students are actively involved in recognizing vocabulary, paying attention to Arabic letter patterns, and applying the mufradat found in the preparation of simple sentences. Digital game-based learning also encourages increased learning motivation, group cooperation, and the creation of a more meaningful vocabulary learning process. Thus, Educaplay Word Search Puzzle can be a relevant alternative digital media in supporting Arabic vocabulary learning at the madrasah level.